ANALYSIS OF OPPORTUNITIES FOR VAT REFORMING IN UKRAINE - Sierbin , Vadym (Socio-economic relations in the digital society, 2021)
Abstract. Ukraine’s independence has become a positive factor in the development of democratic tendenciesin our country and has also significantly changed the economic sector. It is still in the process of being soughtand reformed. In this context, the solution to the problem of improving the tax system is particularly clear, asthe old model of planned economy was unacceptable, and the economic vector has changed from commandto marketing, where international standards of accounting and taxation are actively implemented. At the sametime, today the urgent task of the evolution of the tax system in Ukraine is still to ensure its stability and easycorrection, which in turn should lead to some positive factors: increased budget revenues, improved mechanismsfor collecting and managing value added tax.The article considers the nature and current state of value added tax in Ukraine and the world. It is establishedthat the value added tax is one of the most important taxes. The main provisions of the legislation concerningthe function of value added tax and the main issues related to the collection and administration of taxesare identified. It has been identified that the various aspects of value added tax reform are interlinked, andthat existing methods are not effective enough. As a result, the main problems of modern value added taxmanagement are the underestimation of the economic components of the tax system, complex mechanismsand non-transparent payment systems, which create preconditions for insufficient funding of the country andcontribute to corruption.The possibility and direction of VAT reform in Ukraine are clearly outlined and proposed. Among the mainways to reform VAT, special attention is paid to reducing the value added tax rate, which should lead to lowerdomestic product prices and increased demand. Simplification of the rules for collecting and paying VAT, whichin turn will help solve problems related to VAT administration. As a result, businesses will receive additionalfunds, which they are currently forced to use to attract additional specialists in the legal and financial fields,inspections, court fees, meetings of fiscal authorities, etc. The released resources (and related funds) will increasethe profitability of companies and can be used for further development of specific organizations, which in turnwill increase their profitability and, consequently, increase revenues from value added tax.Keywords: value added tax, VAT, state budget, administration, indirect taxes, reform.JEL Classification H61, H25Formulas: 0; fig.: 2; tabl.: 1; bibl.: 9.
Keywords: valueadded tax; VAT; state budge; administration; indirect taxes; reform